Biliary Strictures: Etiologies and Medical Management - Rodrigues, Terrance; Boike, Justin R. (Seminars in Interventional Radiology, 2021)
Biliary strictures have several etiologies that can broadly be classified into benign and malignant causes. The clinical presentation is variable with strictures identified incidentally on imaging or during the evaluation of routine laboratory abnormalities. Symptoms and cholangitis lead to imaging that can diagnose biliary strictures. The diagnosis and medical management of biliary strictures will be discussed in this article.
Keywords: biliary strictures; hyperbilirubinemia; medical management